2015
DOI: 10.1016/j.psychres.2015.01.031
|View full text |Cite
|
Sign up to set email alerts
|

Mapping non suicidal self-injury in adolescence: Development and confirmatory factor analysis of the Impulse, Self-harm and Suicide Ideation Questionnaire for Adolescents (ISSIQ-A)

Abstract: Non-suicidal self-injury (NSSI) is the deliberate, self-inflicted destruction of body tissue without suicidal intent and an important clinical phenomenon. Rates of NSSI appear to be disproportionately high in adolescents and young adults, and is a risk factor for suicidal ideation and behavior. The present study reports the psychometric properties of the Impulse, Self-harm and Suicide Ideation Questionnaire for Adolescents (ISSIQ-A), a measure designed to comprehensively assess the impulsivity, NSSI behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
0
11

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 31 publications
(56 citation statements)
references
References 72 publications
(105 reference statements)
4
41
0
11
Order By: Relevance
“…Higher scores in each module (factor) indicate the presence and frequency of each of those constructs, while the functions of self-harm subscale indicates the predominant function for those who engage in self-harming behavior: automatic reinforcement or social reinforcement. Studies by Carvalho et al 33 confirmed the factor structure and psychometric properties of the ISSIQ-A, and revealed good internal consistencies (ranging from 0.77 to 0.93) and convergent validity with similar measures. In the current study, Cronbach's alpha ranged from 0.768 (Impulse and Social Function of NSSI subscales) to 0.932 (Automatic Reinforcement subscale).…”
Section: Methodsmentioning
confidence: 82%
See 1 more Smart Citation
“…Higher scores in each module (factor) indicate the presence and frequency of each of those constructs, while the functions of self-harm subscale indicates the predominant function for those who engage in self-harming behavior: automatic reinforcement or social reinforcement. Studies by Carvalho et al 33 confirmed the factor structure and psychometric properties of the ISSIQ-A, and revealed good internal consistencies (ranging from 0.77 to 0.93) and convergent validity with similar measures. In the current study, Cronbach's alpha ranged from 0.768 (Impulse and Social Function of NSSI subscales) to 0.932 (Automatic Reinforcement subscale).…”
Section: Methodsmentioning
confidence: 82%
“…Impulse, Self-harm and Suicide Ideation Questionnaire for Adolescents (ISSIQ-A) 33 The ISSIQ-A is a self-report questionnaire for adolescents, designed to assess risky behaviors (e.g., alcohol and substance use, reckless driving, promiscuous sexual behavior), impulsivity, suicide ideation, and self-harm. The items are assessed on a Likert-type frequency scale (ranging from 0 = never to 3 = always).…”
Section: Methodsmentioning
confidence: 99%
“…Table 1 shows the characteristics of the studies selected for evaluation. Of these 18 studies, 11 were instruments for evaluate NSSI in adolescents: the Self-Injurious Thoughts and Behaviors Interview (SITBI) 22 with one adaptation 23 ; the Self-Harm Behavior Questionnaire (SHBQ) 24 ; the Functional Assessment of Self-Mutila-tion (FASM) 6 with three adaptations [25][26][27] ; the Self-Injury Motivation Scale, Adolescent version (SIMS-A) 28 ; the Alexian Brothers Assessment of Self-Injury (ABASI) 29 ; the Alexian Brothers Urge to Self-Injure Scale (ABUSI) 30 , four adaptations of the instrument Ottawa Self-Injury Inventory (OSI) [31][32][33][34] ; the Risk-Taking and Self-Harm Inventory for Adolescents (RTSHIA) 35 ; the Repetitive Non-Suicidal Self-Injury Questionnaire (R-NS-SI-Q) 36 ; the 6-item measure of Prinstein 37 ; and the Impulse, Self-harm, and Suicide Ideation Questionnaire for Adolescents (ISSIQ-A) 38 . With its publication in 2007, the SITBI 22 became the first instrument intended to measure NSSI among adolescents.…”
Section: Resultsmentioning
confidence: 99%
“…It will be important to extend these findings to some of the more deleterious aspects of BPD. For example, there is growing interest and awareness in constructs such as nonsuicidal self‐injury (e.g., Carvalho et al., ) that are not necessarily particular to BPD. Past research has also established links between other cluster B personality disorders and childhood emotional abuse (e.g., Peng, Zhou, Chen, & Cai, ); it will be necessary to investigate whether or not emotional awareness moderates the relationship between childhood abuse and other personality disorders as we found in the case of BPD.…”
Section: Discussionmentioning
confidence: 99%